Urban Great Tits (Parus major) Show Higher Distress Calling and Pecking Rates than Rural Birds across Europe - Senar, Juan Carlos; Garamszegi, Laszlo Z.; Tilgar, Vallo; Biard, Clotilde; Moreno-Rueda, Gregorio; Salmón, Pablo; Rivas, J. M.; Sprau, Philipp; Dingemanse, Niels J.; Charmantier, Anne; Demeyrier, Virginie; Navalpotro, Helena; et al. (Frontiers in Ecology and Evolution, 2017)
Environmental change associated with urbanization is considered one of the major threats to biodiversity. Some species nevertheless seem to thrive in the urban areas, probably associated with selection for phenotypes that match urban habitats. Previous research defined different “copying styles” in distress behavior during the handling of birds. These behaviors vary along a continuum from “proactive” to “reactive” copers. By studying avian distress behaviors we aimed to broaden our understanding of the relationship between coping styles and urbanization. Using a large-scale comparative study of seven paired rural and urban sites across Europe, we assayed distress behaviors during handling of urban and rural-dwelling populations of the great tit Parus major. We detected no consistent pairwise differences in breath rate between urban and rural habitats. However, urban great tits displayed more distress calling (fear screams) and higher pecking rate (handling aggression) than rural birds. These findings suggest that urban great tits have a more proactive coping strategy when dealing with stressful conditions. This finding is in line with previous studies implying that urban great tits are more explorative, less neophobic and display shorter flight distances than their rural counterparts, representing further aspects of the same “proactive”, coping strategy. Future research should investigate whether reported differences in distress behavior are due to local adaption caused by natural selection or due to phenotypic plasticity.